Efficacy of Tumor-Infiltrating Lymphocytes Combined with IFN-α in Chinese Resected Stage III Malignant Melanoma - Li, Wei (J Immunol Res, 2017)
BACKGROUND: This study aims to explore the efficacy of tumor-infiltrating lymphocytes (TIL) along with interferon-α (IFN-α) to treat stage III malignant melanoma (MM) patients in China. METHODS: Between May 2010 and October 2014, 77 patients of stage III MM who underwent surgery were collected in this study. These patients were divided into two groups: patients who received TIL + IFN-α ± RetroNectin-activated cytokine-induced killer cells (R-CIK) in Arm 1 (n = 27) and IFN-α ± R-CIK in Arm 2 (n = 50) as adjuvant therapy. The primary endpoints were disease-free survival (DFS) time and DFS rates measured at time points of 1, 2, and 3 years. The secondary endpoints were overall survival (OS) rates measured at time points of 1, 2, 3, and 5 years as well as OS as evaluated by Kaplan-Meier. RESULTS: Our results indicated that the median DFS and OS in Arm 1 were significantly better than those in Arm 2. The data also demonstrated that DFS rate and OS rates in Arm 1 were significantly better than those in Arm 2 at all measured time points. CONCLUSION: Patients who undergo surgical excision of stage III MM appear to enjoy prolonged DFS and OS when treated with TIL + IFN-α compared to IFN-α alone.